Case report: Pembrolizumab plus Axitinib related hypothyroid myopathy in two kidney cancer patients - Boutros, Andrea; Vera, Lara; Gatto, Federico; Fornarini, Giuseppe; Zanardi, Elisa (Frontiers in Oncology, 2022)
The first-line therapy in advanced kidney cancer has changed in recent years due to the introduction of combinations of tyrosine kinase inhibitors (TKIs) of vascular endothelial growth factor receptors (VEGFR) and immune checkpoint inhibitors (ICIs). Although immune-related adverse events are well-known, in the case of combination treatments, the determination of which drug is related to an adverse event may be challenging. We reported two cases of patients who developed muscle enzyme elevation in association with hypothyroidism during therapy with pembrolizumab plus axitinib for metastatic kidney cancer. The myopathy rapidly resolved after hormone replacement therapy with levothyroxine. Hypothyroid myopathy is a scarcely known and underreported adverse event. This adverse event may be relevant in the differential diagnosis with immune-related myositis, which has an autoimmune pathogenesis and a potentially fatal course.